Implementation of the Tri Hita Karana Philosophy as a Local Regulatory Mechanism for Sustaining Subak Anggabaya, Denpasar, Bali, Indonesia - Putu Udayani Wijayanti; Ni Wayan Putu Artini; Ketut Budi Susrusa; Ni Luh Devi Darmika Mariyani; I Putu Yoga Darma Rahayu (Universitas Panji Sakti, 2025)
Land conversion remains a major threat, often driven by development and investor disregard for customary laws. Subak Anggabaya, however, enforces officially recognized awig-awig, and is being developed by the Denpasar City Government under the Subak Lestari program to protect agricultural land. While the principles of THK continue to hold firm, the subak system is increasingly pressured by modernization, environmental degradation, and the transformation of rice fields into tourism developments. The concept of Tri Hita Karana comes from three words: Tri (Three), Hita (Happiness), and Karana (Cause). The formulation of the problem in this research is how is the implementation of the Tri Hita Karana philosophy in the awig-awig in Subak Anggabaya. The types of data used in this study is qualitative data. The data collection methods used in this study are as follows: 1). Interviews; and 2) Literature study. The research population consisted of the Pekaseh Gede and three Subak administrators. The method used in this study is qualitative descriptive analysis, a type of qualitative research. The result of this research is the implementation of three aspects of the concept of Tri Hita Karana in Subak Anggabaya, namely: 1) Parhyangan, in the Subak Anggabaya area, the application of the aspect is ceremonial activities carried out from the beginning of agricultural activities to harvest; 2) Pawongan, Subak is an organization where there is often interaction between fellow subak people; 3) Palemahan is an important aspect, especially in maintaining the continuity of nature.